Investigating Transdermal Delivery of Vitamin D(3) - Alsaqr, Ahmed (AAPS PharmSciTech, 2015)
Transdermal delivery of therapeutic amounts of vitamin D(3) is proposed to overcome its variable oral bioavailability, especially for people who suffer from fat malabsorption. The main challenge for this delivery route is to overcome the barrier properties of skin, especially for very lipophilic compounds such as vitamin D(3). In this study, the effect of different penetration enhancers, such as oleic acid, dodecylamine, ethanol, oleic acid in propylene glycol, isopropyl myristate, octyldodecanol, and oleyl alcohol in propylene glycol were evaluated in vitro for their effectiveness in delivering vitamin D(3) through polyamide filter, polydimethylsiloxane membrane, and porcine skin. A diffusion cell was used to study the transdermal permeability of vitamin D(3). Ointment formulations of vitamin D(3) were prepared containing the most widely used penetration enhancers, oleic acid, and dodecylamine. The ointment containing oleic acid as chemical penetration enhancer did not improve delivery compared to control. On the other hand, the formulation containing dodecylamine as a penetration enhancer did improve the transdermal delivery of vitamin D(3). However, statistical significance and an amount high enough for nutritional supplementation purposes were reached only when the skin was pretreated with 50% ethanol. In these conditions, the ointment delivered an amount of 760-ng vitamin D(3) per cm(2) of skin. The research shows promise that transdermal delivery could be an effective administration route for vitamin D(3) when ethanol and dodecylamine are used as penetration enhancers.